Effect of methane enrichment on the performance of a dual fuel CI engine. Issue 3 (17th February 2021) - Vijin Prabhu, A.; Manimaran, R.; Jeba, P.; Babu, R.
ABSTRACT: In this study, the performance characteristics of dual fuel engine are investigated using diesel and bio gas of various methane concentration. A single cylinder compression ignition engine is modified into a biogas–diesel dual fuel engine for experimentation. Experiments were carried out using diesel, raw biogas (CH4 -70.4%), partially purified biogas (CH4 -82.7%) and purified biogas (CH4 -93.8%). Results indicate that the highest amount of diesel replacement (83.45%) was observed in purified biogas when the 60% load was maintained. The higher brake power developed by the engine was observed in purified biogas (5.13 kW) at full loading condition. Of all fuels tesed the purified biogas gave an optimum performance characteristics.